A Parallel-Plate Flow Chamber for Mechanical Characterization of Endothelial Cells Exposed to Laminar Shear Stress - Wong, Andrew K. (Cell Mol Bioeng, 2015)
Shear stresses induced by laminar fluid flow are essential to properly recapitulate the physiological microenvironment experienced by endothelial cells (ECs). ECs respond to these stresses via mechanotransduction by modulating their phenotype and biomechanical characteristics, which can be characterized by Atomic Force Microscopy (AFM). Parallel Plate Flow Chambers (PPFCs) apply unidirectional laminar fluid flow to EC monolayers in vitro. Since ECs in sealed PPFCs are inaccessible to AFM probes, cone-and-plate viscometers (CPs) are commonly used to apply shear stress. This paper presents a comparison of the efficacies of both methods. Computational Fluid Dynamic simulation and validation testing using EC responses as a metric have indicated limitations in the use of CPs to apply laminar shear stress. Monolayers subjected to laminar fluid flow in a PPFC respond by increasing cortical stiffness, elongating, and aligning filamentous actin in the direction of fluid flow to a greater extent than CP devices. Limitations using CP devices to provide laminar flow across an EC monolayer suggest they are better suited when studying EC response for disturbed flow conditions. PPFC platforms allow for exposure of ECs to laminar fluid flow conditions, recapitulating cellular biomechanical behaviors, whereas CP platforms allow for mechanical characterization of ECs under secondary flow.